Effectiveness of MIST with hydroxyapatite and β-tricalcium phosphate in alveolar bone density and osteocalcin level improvement during treatment of infrabony pockets - Aulida Arum Mubarokah; Ahmad Syaify; Sri Pramestri Lastianny (Majalah Kedokteran Gigi Indonesia, 2022)
The minimally invasive surgical technique (MIST) is a method for periodontal regenerative treatment by minimizing trauma so it can preserve vascular supply of the interdental papillae. This study aims to determine the effectiveness of the MIST method with the addition of a combination of hydroxyapatite and β-tricalcium phosphate (HA + β-TCP) in treatment of infrabony pockets in terms of alveolar bone density and osteocalcin levels of gingival crevicular fluid. The study sample was taken from 20 teeth with infrabony pockets (n = 20), which were divided into two groups: 10 teeth treated with MIST and the other group with open flap debridement (OFD). Both groups received combination of HA + β-TCP. The osteocalcin levels of gingival crevicular fluid were checked on day-0 prior to the flap surgery, day-7 and day-14 after flap surgery using the Human Osteocalcin Elisa Kit. Radiological evaluation of alveolar bone density at day-0 and day-90 was done using cone beam computed tomography. Data of osteocalcin levels were analyzed using two-way ANOVA and continued with LSD Post Hoc test, while data of alveolar bone density reduction were analyzed using the Independent t-test parametric test. The results showed that there was no significant difference (p > 0.05) in the values of alveolar bone density between the MIST and OFD groups on day-0 and day-90, while the osteocalcin levels in both groups showed an increase from day-0 to day-7 and a decrease from day-7 to day-14. There was a significant difference (p < 0.05) on day-0 and 7 and day-7 and 14 between MIST and OFD groups. The MIST method with HA + β-TCP was effective and further increases alveolar bone density and osteocalcin levels of gingival crevicular fluid.